Autonomy and intervention : parentalism in the caring life - Kultgen, John H. (Oxford University Press, 1995)
This philosophical treatise explores the place of paternalism in caring for others. It provides guidelines for balancing respect for the recipients' autonomy with the good that can be provided by intervening in their lives.